Climate Litigation in Indonesia: Lessons from the Royal Dutch Shell Case - Prihandono, Iman (Universitas Airlangga, 2024)
This article compares the concept of unlawful act in the Indonesian and Dutch Civil Codes, with specific attention to the notorious decision of the Milieudefensie et al v. Royal Dutch Shell Case. Therein, the Dutch Court applied unwritten law under Article 6:612 of the Dutch Civil Code, calling for reduction in carbon emissions through policy changes by the Shell group. The use of unwritten law allowed for a comprehensive assessment of legal bases, including international soft law instruments, such as the United Nations Guiding Principles on Business and Human Rights. Inspired by such a decision, this article aims to unveil the readiness of Article 1365 of the Indonesian Civil Code in entertaining a similar case. It compares the approach taken in the Milieudefensie et al. v. Royal Dutch Shell Case with pertinent decisions by the Indonesian court concerning the implementation of Article 1365 of the Indonesian Civil Code. Furthermore, it focuses on two prongs of civil liability that are necessary for establishment: 1) unwritten law; and 2) causality. By doing so, this article aims to contribute to the evolving realm of climate litigation, specifically within the framework of civil law.